P34 The minimal clinically important difference of the COPD assessment test. (14th November 2013) - Kon, SSC; Canavan, JL; Clark, AL; Jones, SE; Nolan, CM; Polkey, MI; Man, WDC
Abstract : Background: The COPD (chronic obstructive pulmonary disease) assessment test (CAT) is a simple 8-item, health status instrument (Jones PW et al 2009). It has good psychometric properties and has been shown to be responsive to pulmonary rehabilitation (PR) (Dodd et al 2011) and recovery from exacerbation (Jones PW et al 2011). The CAT has also recently been incorporated into the Global Initiative for Chronic Obstructive Lung Disease (GOLD) combined assessment of COPD, to help assess disease severity. However the minimal clinically important difference (MCID) for the CAT has not been formally established. Aims: The aims of this study were to assess the relationship between change in CAT and change in other health related quality of life (HRQoL) questionnaires and to provide estimates for the MCID. Methods: The CAT, St. George's Respiratory Questionnaire (SGRQ), Chronic Respiratory Questionnaire (CRQ) and Clinical COPD Questionnaire (CCQ) were measured in 565 COPD patients before and after outpatient PR. Paired t tests were used to compare outcomes before and after PR. Spearman rank correlation was used to compare changes in CAT with other HRQoL questionnaires. Using an anchor-based approach and receiver operating characteristic (ROC) curves, the CAT change cut-offs that identified patients achieving the known MCID for other health status questionnaires with PR were identified. Results: The CAT, SGRQ, CRQ and CCQ all significantly improved with PR. CAT change correlated significantly with change in SGRQ, CRQ and CCQ (r = 0.30, -0.44, 0.52 respectively; all p < 0.001). ROC curves consistently identified -2 points as the best cut-off to identify the MCID for the SGRQ (-4 points), CRQ (10 points) and CCQ (-0.4 points) (AUC: 0.65, 0.77 and 0.74 respectively; all p < 0.001–see Fig.1 ). Conclusion: The minimal clinically improvement of the CAT is estimated to be a 2 point decrease.